2011 IEEE Symposium on Artificial Life (ALIFE) 2011
DOI: 10.1109/alife.2011.5954669
|View full text |Cite
|
Sign up to set email alerts
|

Cultural diversity dynamics

Abstract: Abstract-In this work, we are exploring mechanisms that may contribute to cultural dynamics and cultural diversity. To this end, we are experimenting with an extended Axelrod model that uses a Moore neighborhood and heterogeneous sets of cultural features per agent. We are gradually introducing a number of psychologically realistic, basic and more advanced, conceptual models of cultural affinity perception and imitation and show that in many cases the population stabilizes to multi-cultural configurations. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…We are using as basis an Axelrod model of cultural imitation [3][4][5] [6], where an agent is characterized by a number of cultural features, each one of which may take one of several values, called traits, and where an initially fully heterogeneous population (with random traits) may lead eventually to compact cultural groups that are homogeneous internally but with large differences between them, provided that a simple imitation process takes place: an agent may imitate (copy) a trait of a neighbor probabilistically based on the affinity with him (the proportion of traits that coincide). We have modified and extended this model with a Moore neighborhood, heterogeneous sets of cultural features per agent and a number of psychologically realistic, basic and more advanced, conceptual models of cultural affinity perception and imitation [7]. We have shown that in many cases the population stabilizes to multi-cultural configurations and that, in cases of population clashes where two or more culturally contiguous populations meet, the cultural divide may persist, albeit in a relatively weaker form [7] [8].…”
Section: A Rationale and Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…We are using as basis an Axelrod model of cultural imitation [3][4][5] [6], where an agent is characterized by a number of cultural features, each one of which may take one of several values, called traits, and where an initially fully heterogeneous population (with random traits) may lead eventually to compact cultural groups that are homogeneous internally but with large differences between them, provided that a simple imitation process takes place: an agent may imitate (copy) a trait of a neighbor probabilistically based on the affinity with him (the proportion of traits that coincide). We have modified and extended this model with a Moore neighborhood, heterogeneous sets of cultural features per agent and a number of psychologically realistic, basic and more advanced, conceptual models of cultural affinity perception and imitation [7]. We have shown that in many cases the population stabilizes to multi-cultural configurations and that, in cases of population clashes where two or more culturally contiguous populations meet, the cultural divide may persist, albeit in a relatively weaker form [7] [8].…”
Section: A Rationale and Modelmentioning
confidence: 99%
“…We have modified and extended this model with a Moore neighborhood, heterogeneous sets of cultural features per agent and a number of psychologically realistic, basic and more advanced, conceptual models of cultural affinity perception and imitation [7]. We have shown that in many cases the population stabilizes to multi-cultural configurations and that, in cases of population clashes where two or more culturally contiguous populations meet, the cultural divide may persist, albeit in a relatively weaker form [7] [8]. In this paper we repeat some of our previous experiments to investigate the effects of partner selection on these configurations.…”
Section: A Rationale and Modelmentioning
confidence: 99%
See 2 more Smart Citations